2020
DOI: 10.1177/1352458520972557
|View full text |Cite
|
Sign up to set email alerts
|

The use and quality of reporting of propensity score methods in multiple sclerosis literature: A review

Abstract: Background: Propensity score (PS) analyses are increasingly used in multiple sclerosis (MS) research, largely owing to the greater availability of large observational cohorts and registry databases. Objective: To evaluate the use and quality of reporting of PS methods in the recent MS literature. Methods: We searched the PubMed database for articles published between January 2013 and July 2019. We restricted the search to comparative effectiveness studies of two disease-modifying therapies. Results: Thirty-nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…This score has not yet been validated, and we would like to validate it in a new population. We could have used propensity score analyses to control for confounding, but propensity score matching does not yield different estimates compared to conventional multivariate methods (54) and is often used inappropriately in MS research (55).…”
Section: Discussionmentioning
confidence: 99%
“…This score has not yet been validated, and we would like to validate it in a new population. We could have used propensity score analyses to control for confounding, but propensity score matching does not yield different estimates compared to conventional multivariate methods (54) and is often used inappropriately in MS research (55).…”
Section: Discussionmentioning
confidence: 99%
“…14 In MS, a recent review found that an average of eight covariates (range: 3-16) were selected to construct the PS, with the following baseline covariates most frequently used: age, sex, disease duration, number of relapses in the 12 months prior to baseline, Expanded Disability Status Scale (EDSS) score at baseline, and previous treatments. 5 However, only 21% of the reviewed studies reported how the list of covariates was determined. 5 A practical issue with covariate selection for the PS is that relevant confounders are sometimes unavailable in the data source, which violates the condition of no unmeasured confounding.…”
Section: Covariate Selectionmentioning
confidence: 99%
“…5 However, only 21% of the reviewed studies reported how the list of covariates was determined. 5 A practical issue with covariate selection for the PS is that relevant confounders are sometimes unavailable in the data source, which violates the condition of no unmeasured confounding. We provide examples and discuss mitigation strategies in the Supplemental Material, section 2.…”
Section: Covariate Selectionmentioning
confidence: 99%
See 2 more Smart Citations